2015
DOI: 10.1021/acs.est.5b02527
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter Constituents, Nitric Oxide Synthase DNA Methylation and Exhaled Nitric Oxide

Abstract: It remains unknown how fine particulate matter (PM2.5) constituents affect differently the fractional concentration of exhaled nitric oxide (FeNO, a biomarker of airway inflammation) and the DNA methylation of its encoding gene (NOS2A). We aimed to investigate the short-term effects of PM2.5 constituents on NOS2A methylation and FeNO. We designed a longitudinal study among chronic obstructive pulmonary disease (COPD) patients with six repeated health measurements in Shanghai, China. We applied linear mixed-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
91
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 29 publications
(85 reference statements)
7
91
5
1
Order By: Relevance
“…Evidence also suggests effects on methylation specific to airway inflammation: nitric oxide synthase 2a methylation decreased within 24 hours of PM 2.5 exposure (22). Reduced methylation of inflammation genes.was also associated with acute or intermediate-term exposure to air pollutants (19,(21)(22)(23)(24)50).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Evidence also suggests effects on methylation specific to airway inflammation: nitric oxide synthase 2a methylation decreased within 24 hours of PM 2.5 exposure (22). Reduced methylation of inflammation genes.was also associated with acute or intermediate-term exposure to air pollutants (19,(21)(22)(23)(24)50).…”
Section: Discussionmentioning
confidence: 96%
“…Several recent studies have reported PM 2.5 -related reductions in DNA methylation in noncoding repetitive elements, including long interspersed nuclear element-1 (20) and Alu (21), a short interspersed nuclear element, both of which are considered surrogates for global methylation. However, few epidemiologic studies have investigated the associations between PM 2.5 and short-term changes in methylation at specific sites in the DNA, where a cytosine nucleotide is followed by a guanine nucleotide in the sequence of bases along the 5′ to 3′ direction and the nucleotides are separated by 1 phosphate (cytosine-phosphate-guanine (CpG)), that regulate inflammation responses (19,(21)(22)(23)(24). In addition, most epidemiologic studies have relied on outdoor, fixed air-quality monitoring stations, which poorly approximate individual exposures, which in turn depend on patterns of daily activity and microenvironments (25,26).…”
mentioning
confidence: 99%
“…13 Recently, a longitudinal study reported a relationship between decreased methylation at 3 CpG loci located in the nitric oxide synthase 2, inducible (NOS2A) gene and short-term exposures to organic carbon, elemental carbon, NO 3 ¡ , and NH 4 C among 28 patients with chronic obstructive pulmonary disease. 7 A more recent epigenome-wide study by Panni et al on short-and mid-term PM 2.5 exposure among 3 independent cohorts-the US NAS cohort and the German KORA F3 and F4 cohorts-identified 12 CpG sites at a Bonferroni adjusted significance level. 20 Methylation at 9 out of these 12 CpGs showed increases related to PM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The literature to date indicates that DNA methylation may be an important pathway linking particulate matter (PM) to health outcomes. [6][7][8][9][10] For example, changes in patterns of DNA methylation may be associated with processes leading to cardiovascular diseases.. 11,12 There is growing evidence that exposure to PM is associated with global DNA methylation and gene-specific methylation, 6,7,13,14 especially for exposure to metal-rich PM in occupational settings. 15, 16 Yet, little is known regarding how PM exposure affects DNA methylation on a genome-wide level.…”
Section: Introductionmentioning
confidence: 99%
“…To help shed light on the species responsible for adverse health effects, there is an increasing interest to explore the potential differential effects of various constituents (Brunekreef et al, 2005). Currently, the existing evidence on the associations between PM 2.5 constituents and FeNO levels have been limited to the carbonaceous components (Delfino et al, 2010;Jansen et al, 2005) or in Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/envres certain susceptible groups (Chen et al, 2015a;Lin et al, 2011). It remains to be determined if various PM 2.5 constituents differentially modify FeNO levels in healthy general populations.…”
Section: Introductionmentioning
confidence: 99%